Aneurisma intracraniano gigante em criança de nove anos: relato de caso Giant intracranial aneurysm in a nine-year-old child: case report - João Flávio Mattos Araújo; Rinaldo Koester Santori; Alexander Sperlescu; José Luis Cury Marins; Roque José Balbo (Arquivos de Neuro-Psiquiatria)
É relatado o caso de menina de 9 anos de idade com quadro de hemorragia intracraniana devido a aneurisma gigante da porção distai da artéria cerebral média. Aneurismas cerebrais são considerados raros em crianças, principalmente na primeira década de vida. Em crianças, eles tendem a ocorrer principalmente em ramos arteriais periféricos e são frequentemente gigantes. São discutidos os achados clínicos e a patogênese dessa lesão. The case of a 9-year-old girl with intracranianal hemorrhage due to a giant aneurysm of distal middle cerebral artery is reported. Cerebral aneurysms are rare in children, particularly in the first decade of life. Aneurysms in childhood occur more frequently in peripheral branches and they are more often giant in size. Clinical features and pathogenesis of this lesion are discussed.